Retrospective Study of Self Esteem in Patients with Pityriasis Versicolor - Bagus Meurah Suropati; Eko Budi Koendhori; Sawitri Sawitri; Evy Ervianti (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2020)
Background: Pityriasis Versicolor (PV) is a fungal infection of the skin, caused by the Malassezia sp., a genus of fungi. Patients commonly present with bordered skin patches of white, grey, and sometimes brown on their skin surface. The prominent changing of skin colour in exposed areas of the skin may cause feelings of insecurity to the patients and become limelight for other people, impacting their self esteem. Purpose: To evaluate the self esteem profile in PV patients at the dermatovenereology outpatient clinic of Dr. Soetomo General Academic Teaching Hospital Surabaya. Methods: This was a retrospective descriptive study based on medical records of the dermatovenereology outpatient clinic of Dr. Soetomo General Academic Teaching Hospital Surabaya. The data were collected from June 2018 to May 2019. This research evaluates PV patients's profiles by age, sex, education level, occupation, residential environment, site of infection, duration of the infection, and self esteem. The patient's self esteem was assessed using the Rosenberg Self Esteem Scale (RSES). Result: Fiftythree PV patient’s self esteem values were successfully recorded. Of the 53 patients, the score was low in 3 people (5.67%), the normal score in 50 people (94.33%), and no one had a high score. Of the 3 people with low self esteem scores, 2 of them were men, consisting of 1 teenager and 2 adults, having basic education levels, who were students and housewives. The three patients had the infection for more than 3 months and they resided in Tambaksari, Wonocolo, and outside Surabaya. Conclusion: The majority of PV patients at the dermato-venereology outpatient clinic of Dr. Soetomo General Academic Teaching Hospital have normal self esteem scores.